2019
DOI: 10.1111/1556-4029.14012
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Intentional Body Dismemberment in New York City: 1996–2017

Abstract: A review of New York City dismemberment cases occurring between 1996 and 2017 was conducted, which resulted in a total of 55 dismembered decedents in a 22‐year period. Annual trends indicate an average of 2.5 dismembered decedents. Additional results show that 53% of cases involved transection only, 35% involved disarticulation only, and 13% involved a combination of both. When the entire body could be accounted for, the average number of body portions per case was 5.5. Frequent locations for dismemberment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
4
23
1
Order By: Relevance
“…Various studies [14,[20][21][22][23][24] examining the prevalence of criminal dismemberment indicate that such cases are not a rare occurrence and emphasize the need to continue to standardize SFT analytical techniques. In New York City, 55 cases of criminal dismemberment were recorded over a 22-year period (1996-2017), with a ratio of one dismemberment case for every 224 homicide cases and an average of four cases annually [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies [14,[20][21][22][23][24] examining the prevalence of criminal dismemberment indicate that such cases are not a rare occurrence and emphasize the need to continue to standardize SFT analytical techniques. In New York City, 55 cases of criminal dismemberment were recorded over a 22-year period (1996-2017), with a ratio of one dismemberment case for every 224 homicide cases and an average of four cases annually [20].…”
mentioning
confidence: 99%
“…Various studies [14,[20][21][22][23][24] examining the prevalence of criminal dismemberment indicate that such cases are not a rare occurrence and emphasize the need to continue to standardize SFT analytical techniques. In New York City, 55 cases of criminal dismemberment were recorded over a 22-year period (1996-2017), with a ratio of one dismemberment case for every 224 homicide cases and an average of four cases annually [20]. Seidel and Fulginiti [23] recorded eight cases involving criminal dismemberment over a 28-year period (1984-2012) Sweden over a 30-year period (1961-1990), and 134 dismemberment cases over a 51-year period in Japan [14,21,24].…”
mentioning
confidence: 99%
“…Moreover, these studies have not accounted for the number of inhabitants in the region when reporting absolute numbers of mutilation cases, rendering difficulties in comparing their findings with the results in our study. Another study, by Adams et al [6], included only cases with separation of bones and excluded cases with mutilation of noses, breasts, or genitalia, which is considered to be a main feature of offensive mutilations. They compared their number of dismemberments to the average homicide rate and concluded that dismemberment occurs in one in every 224 homicides, which corresponds to 0.4% a lower figure than we found in our study.…”
Section: Comparison To Other International Studiesmentioning
confidence: 99%
“…Some studies have for instance only covered cities or regions in a country whilst not controlling for the total number of homicides or inhabitants in said region. Nonetheless, Adams et al [6] reported 55 dismemberment cases in New York/USA between 1996 and 2017, Konopka et al [7] reported 23 mutilation cases in Cracow/Poland from 1968 to 2005 and Wilke-Schalhorst et al [8] reported 51 cases in Hamburg/ Germany for the period between 1959 and 2016.…”
mentioning
confidence: 99%
“…However, to my knowledge, the concept has gained little traction. Indeed, in a recent review of 55 dismemberments in New York, more than four times the number of dismemberments examined by H€ akk€ anen-Nyholm et al (1), the concept of psychotic dismemberment is not even mentioned (2). Whilst I do not reject the concept per se, I am minded to agree with P€ uschel and Koops (3), and Konopka et al (4) that psychotic dismemberment does not warrant a specific category of its own.…”
mentioning
confidence: 90%